2020
DOI: 10.1002/pi.5982
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and stretchable polyaniline supercapacitor with a high rate capability

Abstract: Flexible electronics are currently highly favored because of their promising applications in flexible displays, artificial electronic skin, wearable devices etc. Exploiting flexible energy storage systems, which are supercapacitors, that have a decent electrochemical performance as well as flexibility and stretchability is essential to promote the development of flexible electronic products. In this work, a flexible and stretchable polyaniline (PANI) supercapacitor based on a conductive stainless steel mesh wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…From these results, it is believed that improvement in the long term cycling performance for Cbz-PANI-1 requires more device optimization. Overall, these results are comparable and even superior to similar symmetric PANI devices made without conductive additives or special structural arrangements, , and other CPs from the literature (Table S4). Operationally, when the symmetric device is fully charged the positive electrode becomes fully oxidized while the negative electrode is simultaneously reduced.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…From these results, it is believed that improvement in the long term cycling performance for Cbz-PANI-1 requires more device optimization. Overall, these results are comparable and even superior to similar symmetric PANI devices made without conductive additives or special structural arrangements, , and other CPs from the literature (Table S4). Operationally, when the symmetric device is fully charged the positive electrode becomes fully oxidized while the negative electrode is simultaneously reduced.…”
Section: Resultssupporting
confidence: 78%
“…Its many attributes include easy and inexpensive preparation, nonredox doping, environmental stability in the doped state, reversible oxidative states, and high electrical conductivity. As a result, PANI is being explored for application in many fields such as sensors, , energy storage devices, corrosion inhibitor, photovoltaic cells, and microwave safeguards and electromagnetic shielding materials. , However, PANI is challenged with two main problems: it undergoes electrochemical aging, which results in electrochemical instability, and it is insoluble in common organic solvents. Reported approaches that render PANI soluble include incorporating solubilizing counterions and blending with solubilizing polymers. , Recently, Mustafin et al reported PANI derivatives with short alkyl chains that were soluble in common organic solvents . While there have been several approaches to address PANI’s insolubility, there are fewer reports that address its electrochemical instability.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Huang et al described 139 other SC using PANI electrodes and a high strain resistant hydrogel (PVA/H 3 PO 4 ) electrolyte. The novel SC was obtained by electrodeposition route, a cost‐effective and facile technique.…”
Section: Polymer and Polymer Composites For Batteries Obtaining And T...mentioning
confidence: 99%
“…Very few achievements on high-rate PANI supercapacitors have been reported. [8][9][10][11] Therefore, it is meaningful to investigate PANI-based supercapacitors for high-rate performance through rational design of the electrode structure, in particular, if such a rationally designed PANI electrode could be fabricated in a scalable approach.…”
Section: Introductionmentioning
confidence: 99%